2017
DOI: 10.1073/pnas.1719369115
|View full text |Cite|
|
Sign up to set email alerts
|

Familial Parkinson’s point mutation abolishes multiple system atrophy prion replication

Abstract: In the neurodegenerative disease multiple system atrophy (MSA), α-synuclein misfolds into a self-templating conformation to become a prion. To compare the biological activity of α-synuclein prions in MSA and Parkinson's disease (PD), we developed nine α-synuclein−YFP cell lines expressing point mutations responsible for inherited PD. MSA prions robustly infected wild-type, A30P, and A53T α-synuclein-YFP cells, but they were unable to replicate in cells expressing the E46K mutation. Coexpression of the A53T and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 30 publications
8
69
1
Order By: Relevance
“…Contributing to this growing field of investigation, we compared strain differences in the synucleinopathies Parkinson's disease (PD) and multiple system atrophy (MSA), two movement disorders characterized by the neuropathological accumulation of α-synuclein in the brain. Using a cell-based assay, we demonstrated that distinct conformations of α-synuclein are present in PD and MSA patient samples [15]. Similar results have been reported by others [16,17].…”
Section: Introductionsupporting
confidence: 89%
“…Contributing to this growing field of investigation, we compared strain differences in the synucleinopathies Parkinson's disease (PD) and multiple system atrophy (MSA), two movement disorders characterized by the neuropathological accumulation of α-synuclein in the brain. Using a cell-based assay, we demonstrated that distinct conformations of α-synuclein are present in PD and MSA patient samples [15]. Similar results have been reported by others [16,17].…”
Section: Introductionsupporting
confidence: 89%
“…patients are incubated in a cell line expressing this particular mutation (33,48). Although it is tempting to suggest that the distinct characteristics of this particular ␣S mutant arise due to the distinct structural conformer the E46K point mutation produces, as suggested by numerous in vitro findings (49)(50)(51)(52)(53)(54), in our studies these differences may have been due to variations in the mouse versus human ␣S protein or in differences in the amount of the ␣S seeding factor in each sample.…”
Section: Fig 11mentioning
confidence: 68%
“…As a previous study reported that antibodies generated against synthetic forms of α‐syn characterized by high molecular weight species have little predictive and, presumably, therapeutic value (Woerman et al . ), future approaches may better approach this question by focusing on lower molecular weight species or isolated species from post‐mortem brain tissue. Most previous studies have employed antibodies targeting monomeric or fibrillar α‐syn.…”
Section: Therapeutic Strategies In Synucleinopathiesmentioning
confidence: 99%
“…In LB disease research, there are a paucity of studies fully characterizing the diversity and complexity of a-syn aggregates in the diseased brain with the aim of understanding those that are of greatest pathogenic relevance. As a previous study reported that antibodies generated against synthetic forms of a-syn characterized by high molecular weight species have little predictive and, presumably, therapeutic value (Woerman et al 2018), future approaches may better approach this question by focusing on lower molecular weight species or isolated species from post-mortem brain tissue. Most previous studies have employed antibodies targeting monomeric or fibrillar a-syn.…”
Section: Therapeutic Strategies In Synucleinopathiesmentioning
confidence: 99%